1971
DOI: 10.1136/sti.47.5.339
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of T. pallidum and its significance in penicillin-treated seropositive late syphilis.

Abstract: The observation of T. pallidum-like organisms reported by Collart, Borel, and Durel (1962, a, b, c, 1964) in the lymph nodes of both men and rabbits in seroreactive treated syphilis and the stimulating work of Smith and Israel (1967 a, b, 1968)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
0
8
0
1
Order By: Relevance
“…Moreover, whilst the clearance of bacterial DNA was measured, it is unknown whether the DNA detected was from living or dead organisms. As T. pallidum is non-culturable, Rabbit Infectivity Testing (RIT), where test animals are injected with clinical material in order to propagate and identify T. pallidum , could have been used to assess persistence following treatment [ 19 , 20 ]. This approach would, however, have required the sacrifice of a large number of animals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, whilst the clearance of bacterial DNA was measured, it is unknown whether the DNA detected was from living or dead organisms. As T. pallidum is non-culturable, Rabbit Infectivity Testing (RIT), where test animals are injected with clinical material in order to propagate and identify T. pallidum , could have been used to assess persistence following treatment [ 19 , 20 ]. This approach would, however, have required the sacrifice of a large number of animals.…”
Section: Discussionmentioning
confidence: 99%
“…Treponemes may persist despite apparently successful treatment indicating that some treponemes may be ‘resting’ or dividing very slowly . 6873 Clinical data are lacking on the optimal dose and duration of treatment and the long-term efficacy of antimicrobials other than penicillin. The recommendations are based mainly on laboratory considerations, biological plausibility, expert opinion, case studies and clinical experience. Parenteral rather than oral treatment has been the treatment of choice because therapy is supervised and bioavailability is guaranteed. Non-penicillin antibiotics that have been evaluated include doxycycline, erythromycin and azithromycin.…”
Section: Management: General Considerationsmentioning
confidence: 99%
“…2,3 The pathogen is not fully eradicated, allowing the occurrence of secondary and tertiary stages of reactivation in a substantial number of untreated individuals. 3 The local and systemic persistence of the pathogen far beyond the healing of local lesions and establishment of ‘chancre immunity’ has been reported by several investigators 4,5 and confirmed in the rabbit 6 and guinea‐pig models of syphilis (submitted for publication). We have shown that the guinea‐pig is a suitable host for studies of experimental syphilis, 7,8 and delineation of mechanisms of immunity.…”
Section: Introductionmentioning
confidence: 94%